Can social interaction constitute social cognition? - Jaegher, Hanne de; Di Paolo, Ezequiel A.; Gallagher, Shaun (Trends in cognitive sciences, 2010)
An important shift is taking place in social cognition research, away from a focus on the individual mind and toward embodied and participatory aspects of social understanding. Empirical results already imply that social cognition is not reducible to the workings of individual cognitive mechanisms. To galvanize this interactive turn, we provide an operational definition of social interaction and distinguish the different explanatory roles - contextual, enabling and constitutive - it can play in social cognition. We show that interactive processes are more than a context for social cognition: they can complement and even replace individual mechanisms. This new explanatory power of social interaction can push the field forward by expanding the possibilities of scientific explanation beyond the individual.
Gesehen am 15.09.2023